ON SOME JOURNALS WRITTEN DURING THE LATIN PRESS BAN - Kalvāne, Skaidrīte (Via Latgalica, 2014)
The work of gathering information about writers and rewriters started soon after the abolition of Latin press ban in 1904, especially actively participating in the process on the 40th and the 50th anniversary. During the 80s of the 20th century a bibliographer and specialist in literature Aleksejs Apīnis named the writers of Press ban time the farmers’ Prometheus.From about 20 currently known rewriters the life and creative work of Andrivs Jūrdžs have been revealed most exhaustively. Many Prometheus are known only by their name, but not the text, that they had recorded. The problematic issue is also the question of how not to mistake the author (a text writer) with the text owner.The aim of the article is to have a closer look at some of the manuscripts, which have been so far kept in private collections and seen as an integral part of family history. The authors of these works are known, so the list of the writers of Latin print ban time will be complemented.In some 20-page notebook a former soldier Jezups Veituls (1845–?) in 1878 recorded two fasting period and two Christmas time songs. The song of 74 verses “Dzismie ap muku kunga Jezu Chrysta” seems as a summary of several Fasting songs, united by a refrain “Atey Jesu, Atey Jesu, Atej Jesu O! prica./ Miłoju tiewi sirds wysa”. The song tells about Saviour’s pathway of pain. The second song – “Pazamud cyłwaks” – calls for a return to God. Both songs have failed to find originals. Scientists have managed to find the origin of Christmas songs – “Pasokat miłi Ganini” and “Pestitoys dzyma”. The first one is the translation of some variant of the Polish song “Powiedzcie, pasterze mili” (from the book “Symfonie anielskie” (“Symphony of Angels”), 1631), the other one is the translation from Polish “Mesjasz przyszedł na świat prawdziwy” (“W Kanie Galilejskiej”), which was read the first time in Latgalian in the book “Eysas łyugszonas un dzismies” (1824). It is one of the few spiritual songs, that were sung at Latgalian weddings.The author of the article finds it essential to search for originals of spiritual songs, because their absence would allow writers to think about the poet’s talent and would enable to see some creative sparkle. Texts are compared with Andrivs Jūrdžs’ recorded works. We would like to believe, that there was an edition of spiritual songs translated under the guidance of some clergyman or organist. References can be found in the Polish Catholic press in the 80s of the 19th century. But it should be inspected separately.Veitulu Jezups, who was 33 years old, when he was recording songs, was a farmer and a skilled carpenter. He graduated from folk school, where it was not taught to read and write in Latvian (Latgalian). What made him write? Was it salary for the recorded text, the lack of songs, or maybe it was still wish for self-actualization? The writer’s great-grandson Ivars Vītols has carried out a valuable research on his family, which will be replenished with a proud of great-grandfather’s belonging to the unique recorder’s circuit of Latin Press Ban time.One of the first known women transcribers during the Latin Press Ban was Anna Laizāne (1873–1958), who acquired the literacy at home. She was a colorful personality, in Taunagas Manor bill book next to a variety of medical prescriptions and incantations suitable for healing, she transcribed so-called heavenly book – with the registration of unfortunate 42 days and divine instructions.The witness of people’s faith in living with superstition is the book written on canvas by the farmer Benedikts Višņevskis (1871–1943), who lived in Atašiene. Heavenly letter transcribed in 1903 (shortly before the abolition of the press ban) revealing many promises and also threats shows the time, when faith is suppressed and books are banned, but superstition replaces enlightenment. But the recorders daring to get into the unknown world through print signs and incomprehensible expressions of rewritable sources must be accordingly evaluated. A small cloth book has been used as an amulet, so it is a value for another Višņevskis family. The work transcribed by B. Višņevskis is the evidence of the existence of hitherto unmentioned heavenly books or genre of letters in Latgalian spiritual literature.The works of Press Ban time can also be found today – 110 years after the abolition of the ban, but still there are many, including still unknown and undiscovered written evidences of the life of people at the end of the 19th century – at the beginning of the 20th century.